The Impact of Microcredit Loans on School Enrolment in Bangladesh. Issue 9 (1st September 2020) - Kandulu, John; Wheeler, Sarah; Zuo, Alec; Sim, Nicholas
Abstract: Human capital investment, especially in education, is a well-known precursor of economic growth in developing countries. In recent years, there has been a proliferation of microfinance programmes, yet evidence on whether microfinance leads to increased educational investment is tenuous at best. We utilise a large-scale cross-sectional household dataset from Bangladesh and geospatial data to study how microcredit participation and increasing microcredit incomes – that is, the extensive and intensive margins of microcredit – affects the probability of children's school enrolment. The causal influence of microcredit participation on enrolments was estimated by utilising the propensity score matching (PSM) technique – a quasi-experimental treatment effects model. Whilst microcredit participation, the extensive margin, did not significantly influence the likelihood of school enrolment for boys, it increased girls' enrolment. Further, microcredit income, the intensive margin, had a stronger influence on girls' and younger siblings' enrolment than on boys' and older siblings' enrolment. Omission of spatial influences can overstate microcredit influence on enrolment; while not utilising PSM can underestimate the influence of microcredit participation on enrolment. Results suggest policies that focus solely on increasing microcredit participation, without increasing the amount of microcredit incomes accessed by households, may be less effective at improving child education outcomes.